RISE: MatE2U: community outreach by the Maternofoetal and Embryo Research Group (MatE) / Prof. Dr Noor Ashikin Mohamed Noor Khan - Mohamed Noor Khan, Nor Ashikin (Office of the Deputy Vice-Chancellor (Research & Innovation), 2021)
MatE as a multidisciplinary research group in the niche are of reproductive biology and medicine works to advance the understanding of reproductive health and well-being in the community by carrying out MatE2U, its outreach programme.